Inter-laboratory assessment by trained panelists from France and the United Kingdom of beef cooked at two different end-point temperatures. (December 2016) - Gagaoua, Mohammed; Micol, Didier; Picard, Brigitte; Terlouw, Claudia E.M.; Moloney, Aidan P.; Juin, Hervé; Meteau, Karine; Scollan, Nigel; Richardson, Ian; Hocquette, Jean-François
Abstract: Eating quality of the same meat samples from different animal types cooked at two end-point cooking temperatures (55 °C and 74 °C) was evaluated by trained panels in France and the United Kingdom. Tenderness and juiciness scores were greater at 55 °C than at 74 °C, irrespective of the animal type and location of the panel. The UK panel, independently of animal type, gave greater scores for beef flavour (+ 7 to + 24%, P  < 0.001) but lower scores for abnormal flavour (− 10 to − 17%, P  < 0.001) at 74 °C. Abnormal flavour score by the French panel was higher at 74 °C than at 55 °C (+ 26%, P  < 0.001). Irrespective of the data set, tenderness was correlated with juiciness and beef flavour. Overall, this study found that cooking beef at a lower temperature increased tenderness and juiciness, irrespective of the location of the panel. In contrast, cooking beef at higher temperatures increased beef flavour and decreased abnormal flavour for the UK panelists but increased abnormal flavour for the French panel. Highlights: Tenderness and juiciness scores of beef meat from heifers, steers and young bulls were greater at 55 °C than 74 °C. With the UK panel, beef flavour was greater and abnormal beef flavour lower at 74 °C than at 55 °C. With the French panel, abnormal beef flavour was greater at 74 °C than at 55 °C.